Measuring the Application Readiness Level of AKKU Online Mobile Attendance System using HOT-fit Method - Tawar; Yolanda Sabrina Salma; Jehanie May Macasawang (The Indonesian Institute of Science and Technology Research, 2022)
The application of attendance in an institution is necessary to determine the attendance of employees and all staff. The AKKU Mobile online attendance application is an application intended for teachers. However, application users found several problems related to the quality of application services, such as facial scans were not accurate and application errors. The purpose of this study is to determine the level of readiness of the application of the AKKU Mobile application. This measurement uses ARL (Application Readiness Level). The approach used in this research is HOT FIT. Respondents are teachers who use the AKKU Mobile application as many as 173 people. The instrument used was a questionnaire distributed after going through the validity and reliability tests. The results showed that the ARL value on the Human dimension was 73.19%, the organization was 78.37%, and the Technology dimension was 70.58%. The average ARL of human, organization and technology is 74% which is in the pretty good category, or the application execution is successful. However, it is necessary to make modifications and improvements based on the suggestions given so that the ARL value increases, which impacts the quality of the attendance process.